Establishment of Aedes (Ochlerotatus) scapularis (Diptera: Culicidae) in Mainland Florida, With Notes on the Ochlerotatus Group in the United States. Issue 2 (23rd November 2020) - Reeves, Lawrence E; Medina, Johana; Miqueli, Evaristo; Sloyer, Kristin E; Petrie, William; Vasquez, Chalmers; Burkett-Cadena, Nathan D
Abstract: Aedes scapularis (Rondani), a widespread neotropical vector mosquito species, has been included in the mosquito fauna of Florida on the basis of just three larval specimens that were collected in the middle Florida Keys in 1945. Here, we report numerous recent collections of immature and adult Ae. scapularis from multiple locations in two counties of southern Florida. These specimens represent the first records of Ae. scapularis from mainland Florida and the first records of the species in the state since the initial detection of the species 75 yr ago. Collections of both larvae and adults across several years indicate that Ae. scapularis is now established in Broward and Miami-Dade Counties. These contemporary records of this species in Florida may represent novel dispersal and subsequent establishment events from populations outside the United States or a recent reemergence of undetected endemic populations. To confirm morphological identification of Ae. scapularis specimens from Florida, the DNA barcoding region of the cytochrome c oxidase subunit I gene (COI) was sequenced and compared to all other Ochlerotatus Group species from the United States, specifically Aedes condolescens Dyar and Knab (Diptera: Culicidae), Aedes infirmatus Dyar and Knab (Diptera: Culicidae), Aedes thelcter Dyar (Diptera: Culicidae), Aedes tortilis (Theobald) (Diptera: Culicidae), and Aedes trivittatus (Coquillett) (Diptera: Culicidae). Molecular assays and sequencing confirm morphological identification of Ae. scapularis specimens. Maximum likelihood phylogenetic analysis of COI and ITS2 sequences place Florida Ae. scapularis in a distinct clade, but was unable to produce distinct clades for Florida specimens of Ae. condolescens and Ae. tortilis. Graphical Abstract: